Asymptotic estimates for the best trigonometric and bilinear approximations of classes of functions of several variables - Romanyuk, A. S.; Romanyuk, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We obtain exact order estimates for the best M-term trigonometric approximations of the Besov classes B_∞,θ^r in the space L_q. We also determine the exact orders of the best bilinear approximations of the classes of functions of 2d variables generated by functions of d variables from the classes B_∞,θ^r with the use of translation of arguments.